Early Survival of Two High-Porosity Acetabular Components after Total Hip Arthroplasty Revision - Elsharkawy, Karim A.; Hadley, Mike; Gad, Bishoy; Styron, Joseph; Klika, Alison; Higuera, Carlos (The Journal of Hip Surgery, 2017)
Total hip arthroplasty (THA) revision rates remain high and are expected to increase. Different ingrowth surfaces including tantalum and titanium have been introduced to improve fixation and survival. Promising results have been shown with tantalum. This study was conducted to compare the survivorship of titanium and tantalum components after revision THA. A retrospective review of all THA revision cases from January 2002 to December 2010 was performed. Cases, where the questioned components were used, were enlisted in a single continuous cohort. A minimum of 2-year follow-up was required for inclusion. Patients were compared in two groups: titanium versus tantalum components, with the endpoint defined as any failure requiring acetabular component removal. A total of 118 patients were analyzed and included 64 patients in the tantalum group and 56 patients in the titanium group. The average length of follow-up was 50.4 months for both groups. Cases, where tantalum implants were used, were more likely to have a worse acetabular bone loss (p = 0.005). The main cause of index revision was aseptic loosening followed by infection. At the latest follow-up, survivorship was very similar in appearance and failed to achieve statistical difference (log-rank p = 0.1146). Among the variables assessed as potential predictors of failure, only the number of prior revisions was statistically significant (p = 0.004). The high-porosity titanium acetabular components demonstrate same survivorship at 2-year follow-up as the tantalum cups in the setting of revision THA. Only the number of prior revisions was significantly associated with increased failure rate.
Keywords: total hip arthroplasty; high porosity; survivorship